2018
DOI: 10.1007/s11999.0000000000000067
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Joint Line in TKA is Associated With Mid-flexion Laxity: A Study in Cadaver Knees

Abstract: When recutting the distal and posterior femur and downsizing the femoral component, surgeons should be aware that this action might increase the laxity in mid-flexion, even if the knee is stable at 0° and 90°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 50 publications
2
72
2
Order By: Relevance
“… 20 Furthermore, an orthogonal distal femoral resection may raise the medial joint line and cause mid-flexion instability. 21 …”
Section: Introductionmentioning
confidence: 99%
“… 20 Furthermore, an orthogonal distal femoral resection may raise the medial joint line and cause mid-flexion instability. 21 …”
Section: Introductionmentioning
confidence: 99%
“…The influencing factors on the knee joint biomechanics are difficult to analyse under reproducible conditions for a variety of reasons. Currently, knee joint stability is qualitatively assessed intraoperatively by the surgeon via manual varus-valgus and anterior-posterior stress testing at 0° and 90° knee flexion, while the stability in the mid-flexion range is not quantitatively considered 33 . In addition to intraoperative examinations, knee joint stability can be investigated using computational, experimental, or clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…During surgery, clinicians are only able to subjectively examine the knee joint by analysing the flexion and extension gap, however, without the capability to quantitatively evaluate neither knee kinematics nor kinetics 33 . Furthermore, in-vitro studies lack the ability to analyse the impact of isolated influencing factors on the overall musculoskeletal dynamics in terms of reproducibility, and most of these studies do not consider the physiological soft tissue response during dynamic activities 33–37 . Such in-vivo measurements are ethically not possible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a reduced posterior condylar offset (PCO) and subsequent joint line elevation will result in coronal laxity in the mid-flexion range since the axis for rotation of the knee is proximalized and ventralized ( Fig. 1) [14]. The MCL isometry can only be preserved by fully restoring the medial PCO and the medial joint line height.…”
Section: Aims Of the Flexion First Balancer Techniquementioning
confidence: 99%